Agroecological management of a soil‐dwelling orthopteran pest in vineyards. (21st February 2017) - Nboyine, Jerry Asalma; Boyer, Stephane; Saville, David J.; Wratten, Stephen David
Abstract: The efficacy of different combinations of undervine and inter‐row treatments for managing a soil‐dwelling orthopteran pest, weta ( Hemiandrus sp.), in vineyards was investigated over 2 seasons. This insect damages vine buds, thus reducing subsequent grape yield. The undervine treatments comprised pea straw mulch, mussel shells, tick beans [ Vicia faba Linn. var minor (Fab)], plastic sleeves on vine trunks (treated control) and control (no intervention), while inter‐rows contained either the existing vegetation or tick beans. Treatments were arranged in a randomized complete block design with 10 replicates. Data were collected on weta densities, damage to beans and components of yield. The latter were numbers of bud laid down per vine, shoots per bud, clusters per shoot, grape bunches per vine, bunch weight and yield. The undervine treatments significantly affected all variables except the number of shoots per bud. In contrast, none of the variables was significantly affected by the inter‐row treatments or their interaction with undervine treatments, apart from weta density. At the end of the experiment, weta density in the shell treatment was about 58% lower than in the control. As a result, there was about 39% significant yield increase in that treatment compared to the control. Although the undervine beans and sleeves treatments increased yield, there were no reductions in weta density. With undervine beans, the insect fed on the bean plants instead of vine buds. Thus, yield in that treatment was approximately 28% higher than in the control. These results demonstrate that simple agroecological management approaches can reduce above‐ground damage by soil‐dwelling insects.